2019
DOI: 10.2147/ppa.s202173
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient-reported outcomes in schizophrenia patients treated with once-monthly extended-release risperidone in a long-term clinical study</p>

Abstract: Purpose RBP-7000 (PERSERIS™) is a once-monthly subcutaneous extended-release risperidone formulation approved by the United States Food and Drug Administration for the treatment of schizophrenia in adults. The objective of this study was to describe the long-term impact of RBP-7000 on health-related quality of life (HRQoL), subjective well-being, treatment satisfaction and medication preference in patients with schizophrenia. Patients and methods HRQoL was derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Also, previous studies have shown that switching from oral risperidone to LAI risperidone improves health-related quality of life (HRQoL) in patients with schizophrenia [ 10 , 11 ]. In the 52-week multicenter Phase 3 trial of 120 mg RBP-7000, over two-thirds of patients reported high satisfaction with RBP-7000 throughout the study, with HRQoL scores close to the general population [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, previous studies have shown that switching from oral risperidone to LAI risperidone improves health-related quality of life (HRQoL) in patients with schizophrenia [ 10 , 11 ]. In the 52-week multicenter Phase 3 trial of 120 mg RBP-7000, over two-thirds of patients reported high satisfaction with RBP-7000 throughout the study, with HRQoL scores close to the general population [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical efficacy, safety, and tolerability of RBP-7000 injections for the treatment of acute schizophrenia have been demonstrated in Phase 3 trials consisting of an 8-week, double-blind, placebo-controlled, randomized study [ 13 15 ] and a 52-week, open-label, long-term safety study [ 16 ]. In both studies, participants reported high satisfaction with and preference for RBP-7000 as compared with their most recent pre-study antipsychotic medication [ 17 , 18 ]. Also, participants’ overall well-being and health-related quality of life were significantly greater after treatment with RBP-7000 compared with placebo [ 17 ] and were stable over time with long-term treatment [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of change in HRQL, individual or aggregate, has been used to evaluate health interventions in a wide range of conditions and populations (e.g. [3][4][5][6][7]). Inaccurate measurement of change in HRQL may therefore affect clinical practice and health care, and ultimately the quality of care and HRQOL of patients.…”
Section: Introductionmentioning
confidence: 99%